Assessment of Manifestations of Temporomandibular Joint Involvement in Rheumatoid Arthritis Patients - B Movahedian; M Razavi; A Movahedian; M Moeini (Isfahan University of Medical Sciences, 2006)
•Introduction: There are various reports regarding the frequency of Temporomandibular joint (TMJ)involvement in Rheumatoid Arthritis (RA). Manifestations of TMJ involvement, which was investigatedin this study, are: joint pain and sounds, muscles tenderness, morning stiffness, decreased force bite,and radiographic changes.•Methods and Materials: 80 RA patients and 80 normal persons were included as case and controlgroups respectively. The diagnosis of RA was determined according to the criteria of American Collegeof Rheumatology (1987) and confirmed by a rheumatologist. Inclusion criteria for control group weresimilarity of age and sex with RA group, and no history of RA or other bone - joint diseases.All patients were assessed for clinical sings and symptoms of TMJ involvement.•Results: In all aspects, the frequency of TMJ involvement was significantly higher in RA group thancontrol group (p<0.00l). Crepitus was the most prevalent joint sound among RA patients.The incidence of TMJ manifestations, increased with increasing age and duration of RA (p<0.00l).61.2% of RA patients had at least one of the 4 signs of TMJ involvement, including pain, sounds,muscle tenderness and limited opening. In control group the prevalence of this finding was 38.7%. 61%of RA patients had bilateral involvement.•Conclusion: According to this study, prevalence of TMJ involvement is significantly higher in RApatients than normal individuals. However, patients may not complain from joint pain or muscletenderness, but there may be other signs and symptoms such as limited mouth opening and jointsounds- which could be indicative of TMJ problems. According to the results, the frequency of TMJinvolvement increased with increasing age and duration of RA affliction.•Key words: Rheumatoid arthritis, TMJ, TMJ involvement, TMJ disorders.